Peningkatan Hasil Belajar Tema Benda di Sekitarku Melalui Metode Pembelajaran Project Based Learning Kelas III SDN Rejosari 03 - Setiawan, Odditya (Universitas Sebelas Maret, 2020)
This research was motivated by the monotonous and boring state of online learning in class III. Teacher Student learning outcomes also show an average below the KKM. Formulation of the problem